STUDI KONVERSI ENERGI PEMADATAN TANAH DENGAN MODIFIED PROCTOR METHOD UNTUK TANAH PASIR BERLEMPUNG - Ulfa, Siti Zahhara; Adha, Idharmahadi; Setyanto, Setyanto (Universitas Lampung, 2017)
Related to increased of society economics and the growth rate of vehicles, this needs to be balanced with facilities of transportation. So, a new road or repair existing road is needed. The physical and mechanical conditions of soil are closely related to the construction. It caused the soil has a very crucial role in supporting the construction. To obtain good quality pile of soil, soil compaction is required to stabilize against both structural or non-structural loads. In this study comparing the modified proctor method soil compaction energy with modified press compactor tools.The soil samples used is from Tirtayasa Region Sukabumi District Bandar Lampung, it consists of twelve samples used for modified press compactor tools tests, with pressure used are 5 MPa, 10 MPa, 15 MPa, and 20 MPa. For every pressure conducted for 3 soil samples.Laboratory experiment result shows that the maximum volume weight (γdmaks) of 1,42 gr/cm3 amount on modified proctor method tests with the results on modified press compactor tools obtain pressure value of 7 MPa value and the pressure on sheep foot rifling machine of 6,9 N/mm2.KEYWORDS : Modified Proctor, Modified Press Compactor Tools, Compaction, Soil Pile.